Work & life stress experienced by professional workers during the pandemic: a gender-based analysis - Corrente, Melissa; Park, Jungwee; Akuamoah-Boateng, Henrietta; Atanackovic, Jelena; Bourgeault, Ivy L. (Université d'Ottawa | University of Ottawa, 2024)
Abstract The COVID-19 pandemic impacted work and home life exacerbating pre-existing stressors and introducing new ones. These impacts were notably gendered. In this paper, we explore the different work and home life related stressors of professional workers specifically as a result of the COVID-19 pandemic through the gender-based analysis of two pan Canadian surveys: The Canadian Community Health Survey (2019, 2020, 2021) and the Healthy Professional Worker Survey (2021). Analyses revealed high rates of work stress among professional workers compared to other workers and this was particularly notable for women. Work overload emerged as the most frequently selected source of work stress, followed by digital stress, poor work relations, and uncertainty. Similar trends were noted in life stress among professional workers, particularly women. Time pressure consistently stood out as the primary source of non-work stress, caring for children and physical and mental health conditions. These findings can help to develop more targeted and appropriate workplace mental health promotion initiatives that are applicable to professional workers taking gender more fully into consideration.